Структурно-анатомічні адаптації листків вічнозелених видів роду Rhododendron L. (Ericaceae Juss.) - Shumyk, M.I.; Il'ins'ka, A.P.; Ostapyuk, V.M.; Zhuravskiy, R.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2015)
The structural and anatomical adaptations of leaves of two evergreen species of the genus Rhododendron L. (R. ponticum L. and R. searsiae Rehder et E.H. Wilson.) are studied. These rhododendrons grow in different natural areas, belong to celestial ecotops of various altitudes, but are characterized identical frost- and winter hardiness. The most characteristic structural-foliar and diagnostic evidences are defined of each species. A thick leaf, multilayered mesophyll, the developed palisade parenchyma, a two-layer adaksial epiderma, the expressed cuticle, reinforced external walls of an epiderma indicate ability of R. ponticum to maintain intensive insolation. The similar anatomic structure of leaves is peculiar to R. searsiae. Leaves are well adapted for intensive insolation, their anatomic structure indicates growth of a look in the conditions of well humidified substratum and air. Protective structures from an excessive transpiration are observed at both types: two-layer epidermal tissue, peltat ferruterous scales, the developed cuticle and thick-walled epidermal tissue. These structures define resistance of types to negative temperatures. Аn anatomic structure of leaves can be used for definition of types in a vegetative state.